Superconvergence of iterated numerical solutions using wavelets - Supot Seebut (2018)
In this paper, we examine the superconvergence property of iterates of numerical solutions to both Fredholm integral equations of the second kind and to nonlinear Hammerstein equations. The iterates are obtained by applying a class of multiwavelets developed by Alpert.